The ethanolic extract of Corylus avellana L. drives a microRNA-based cytotoxic effect on HepG2 hepatocarcinoma cells - Maria Pierdomenico; Loretta Bacchetta; Barbara Benassi (Natural Product Research, 2025)

Associations between fine particulate matter, gene expression, and promoter methylation in human bronchial epithelial cells exposed within a classroom under air-liquid interface - Massimo Santoro; Francesca Costabile; Maurizio Gualtieri; Matteo Rinaldi; Marco Paglione; Maurizio Busetto; Gianluca Di Iulio; Luca Di Liberto; Monica Gherardi; Armando Pelliccioni; Paolo Monti; Benassi Barbara; et al. (Environmental Pollution, 2024)

Anti-inflammatory effect of a pomegranate extract on LPS-stimulated HepG2 cells - Maria Pierdomenico; Costanza Riccioni; Barbara Benassi (Natural Product Research, 2024)

Epigenetic-based antioxidant effect of an ethanolic extract of Corylus avellana L . on THLE-2 human primary hepatocytes - Barbara Benassi; Loretta Bacchetta; Oliviero Maccioni; Francesca Pacchierotti (Natural Product Research, 2023)

Experimental and in silico evaluations of the possible molecular interaction between airborne particulate matter and SARS-CoV-2 - Alice Romeo; Roberto Pellegrini; Maurizio Gualtieri; Barbara Benassi; Massimo Santoro; Federico Iacovelli; Milena Stracquadanio; Mattia Falconi; Carmela Marino; Gabriele Zanini; Caterina Arcangeli (Science of The Total Environment, 2023)

Exposure of the SH-SY5Y Human Neuroblastoma Cells to 50-Hz Magnetic Field: Comparison Between Two-Dimensional (2D) and Three-Dimensional (3D) In Vitro Cultures - Claudia Consales; Alessio Butera; Caterina Merla; Emanuela Pasquali; Vanni Lopresto; Rosanna Pinto; Maria Pierdomenico; Mariateresa Mancuso; Carmela Marino; Barbara Benassi (Molecular Neurobiology, 2021)
We here characterize the response to the extremely low-frequency (ELF) magnetic field (MF, 50 Hz, 1 mT) of SH-SY5Y human neuroblastoma cells, cultured in a three-dimensional (3D) Alvetex ® scaffold compared to conventional two-dimensional (2D) monolayers. We proved that the growing phenotype of proliferating SH-SY5Y cells is not affected by the culturing conditions, as morphology, cell cycle distribution, proliferation/differentiation gene expression of 3D-cultures overlap what reported in 2D plates. In response to 72-h exposure to 50-Hz MF, we demonstrated that no proliferation change and apoptosis activation occur in both 2D and 3D cultures. Consistently, no modulation of Ki67 , MYCN , CCDN1 , and Nestin, of invasiveness and neo-angiogenesis-controlling genes ( HIF-1α , VEGF , and PDGF ) and of microRNA epigenetic signature (miR-21-5p, miR-222-3p and miR-133b) is driven by ELF exposure. Conversely, intracellular glutathione content and SOD1 expression are exclusively impaired in 3D-culture cells in response to the MF, whereas no change of such redox modulators is observed in SH-SY5Y cells if grown on 2D monolayers. Moreover, ELF-MF synergizes with the differentiating agents to stimulate neuroblastoma differentiation into a dopaminergic (DA) phenotype in the 3D-scaffold culture only, as growth arrest and induction of p21 , TH , DAT , and GAP43 are reported in ELF-exposed SH-SY5Y cells exclusively if grown on 3D scaffolds. As overall, our findings prove that 3D culture is a more reliable experimental model for studying SH-SY5Y response to ELF-MF if compared to 2D conventional monolayer, and put the bases for promoting 3D systems in future studies addressing the interaction between electromagnetic fields and biological systems.

Fifty-Hertz Magnetic Field Affects the Epigenetic Modulation of the miR-34b/c in Neuronal Cells - Claudia Consales; Claudia Cirotti; Giuseppe Filomeni; Martina Panatta; Alessio Butera; Caterina Merla; Vanni Lopresto; Rosanna Pinto; Carmela Marino; Barbara Benassi (Molecular Neurobiology, 2018)

A Microdosimetric Study of Electropulsation on Multiple Realistically Shaped Cells: Effect of Neighbours - Agnese Denzi; Francesca Camera; Caterina Merla; Barbara Benassi; Claudia Consales; Alessandra Paffi; Francesca Apollonio; Micaela Liberti (The Journal of Membrane Biology, 2016)

Extremely Low Frequency Magnetic Field (ELF-MF) Exposure Sensitizes SH-SY5Y Cells to the Pro-Parkinson’s Disease Toxin MPP+ - Barbara Benassi; Giuseppe Filomeni; Costanza Montagna; Caterina Merla; Vanni Lopresto; Rosanna Pinto; Carmela Marino; Claudia Consales (Molecular Neurobiology, 2016)

A proposed integrated systems approach to the radiation biology of cosmic interest: biophysics and molecular characterization of tissues irradiated with 14 MeV neutrons - Valerio Licursi; Emiliano Fratini; Barbara Benassi; Mariangela Cestelli-Guidi; Claudia Consales; Augusto Marcelli; Chiara Mirri; Rodolfo Negri; Roberto Amendola (Rendiconti Lincei. Scienze Fisiche e Naturali, 2014)